Kingston Hospital: A Community Hospital in Upper Canada in mid-Nineteenth Century - Low, James (Ontario History)

(untitled) (The Ontario Historical Society, 2015)
By the mid-nineteenth century, the major population centres in Upper Canada had built the first hospitals and a small number of British trained physicians provided care. The admission and death records of the Kingston Hospital for 1853-1866 provide insight into those admitted to hospital and the nature of their ailments. Infection based on the admission diagnosis of fevers, venereal disease and inflammatory lesions in the general and organ system categories was the major illness occurring in these patients, highlighting the importance of infection at a time when there was a growing understanding of its nature and cause. The remaining patients were more frequently diagnosed with cardiac and neurological lesions and cancers that would later become more important as lifespans increased. Hospital mortality was similar to that in the established voluntary hospitals in Britain.